Fish ecology of mesophotic coral ecosystems - Andradi-Brown, D (2017)
Mesophotic coral ecosystems (MCEs; reefs 30-150 m depth) are largely unstudied. This thesis uses the shallow reef to MCE depth gradient around Utila, Honduras, to address research questions in three themes: (i) understanding fish community ecological processes on MCEs; (ii) evaluating effective survey techniques for MCE fish research; and (iii) exploring the role of MCEs in the western Atlantic lionfish invasion. Around Utila, herbivorous reef fish declined with increasing depth, but remained present on MCEs, suggesting a possible role in structuring mesophotic benthic communities. To test this I artificially excluded fish from areas of the reef with controls for changing light levels. The results indicate strong effects of light availability on MCE hard coral, macroalgal and sponge coverage, while little detectable effects of fish exposure. Fish surveys play a crucial role in informing reef management, yet few studies consider how biases in survey techniques varies across depth gradients. I explored differences between baited-remote underwater video (BRUV) and diver-operated video (DOV) finding BRUVs consistently recorded more species regardless of depth, but that DOV is likely better for surveys of herbivores. I also assessed fish responses to divers using open-circuit SCUBA or closed-circuit rebreathers (CCR) and, while both recorded similar fish abundances, CCR divers were able to approach fish more closely. In addition, I conducted a meta-analysis identifying widespread invasion of western Atlantic MCEs by Indo-Pacific lionfish, with similar relative abundance distributions across the depth gradient to native range sites. Around Utila, MCE lionfish occurred at greater densities than on shallow reefs, with MCE individuals larger and more mature than their shallow counterparts. This suggests deeper lionfish populations may represent an extension of ontogenetic migrations, and act as a disproportionately large source of new lionfish recruits. Overall, this thesis provides insights applicable to the western Atlantic region more generally and highlights the need for MCEs to be considered by reef managers.